COST-EFFECTIVE SERVICE EXCELLENCE: EXPLORING THE RELATIONSHIPS AMONG RESTAURANTS' OPERATIONAL EFFICIENCY, SIZE AND SERVICE QUALITY (The South East European Journal of Economics and Business, 2019)
The main goal of this study is to investigate whether higher (cost-effective) operational efficiency in restaurants can be achieved without lowering the perceived level of service quality. This study also investigates the importance of restaurants' size on operational efficiency and on the perceived level of service quality level. We present the methodological procedures used to investigate the relationships among restaurants' operational efficiency, size, and service quality after presenting the conceptualization of the cost-effective service excellence (CESE) research construct. The restaurants' efficiency was assessed using Data Envelopment Analyses and the DINESERV tool was implemented to analyse guests' perceptions of service quality. Guests of low- and high- efficient restaurants perceive service quality based on the same quality dimensions. Based on the structural equation modelling, it is clearly evident that CESE can be achieved in the restaurant industry. The restaurant size has proven to influence restaurants' operational efficiency and guests’ quality perceptions.